Evaluation of the sensitivity of Faust method and spontaneous sedimentation for the diagnosis of giardiasis - Lopes Ananias, Fabíola (Revista Cubana de Medicina Tropical, 2017)
Introduction: in a routine clinical laboratory, parasitological methods are used for the detection and diagnosis of intestinal parasitic diseases. Objective: To evaluate the sensitivity of Faust´s and the spontaneous sedimentation methods (Hoffman, Pons and Janer). Methods: a comparative study was developed. The analyzes were made on control samples containing Giardia lamblia from the Laboratory of Clinical Pathology of Santa Casa de Misericórdia of São Paulo and processed again in the clinical laboratory at the University of Nove de Julho by 18 analysts. Results: the statistical difference estimated by the McNemmar test (p= 0.0156) and the Bland and Altman statistics through the graphical analysis showed low correlation between the techniques applied in this research, which indicates that the Faust technique is the most sensitive for the detection of protozoan cysts. Conclusions: this paper is relevant for the quality control of laboratory procedures to be applied to minimize the risk of false positives and false negatives.